2023
DOI: 10.21608/jabps.2022.161607.1165
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of Actinomycetes and Their Secondary Metabolites: A Comprehensive Review

Abstract: Background: Among prokaryotes, Actinomycetes are one of the most explored microorganism due to their capability of novel bioactive secondary metabolites production. Actinomycetes secondary metabolites are known for their role in different cellular, physiological and biological processes. Main body: Actinomycetes are most widely distributed in natural ecosystem habitats such as soil, hypersaline soil, rhizosphere soil, freshwater, limestone, volcanic cave, marine sediments, sponges, and desert. Actinomycetes bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Actinomycetes play a crucial role in the production of various bioactive secondary metabolites. Research has shown that hypersaline soil, rhizosphere soil, marine sediments, and deserts are rich sources of diverse secondary metabolites due to the presence of Actinomycetes species, especially those found in near-extreme conditions, which are highly valued for their potential in novel secondary metabolite production (Khan et al, 2022). Efforts have been made to explore new habitats for screening actinomycete strains capable of producing novel secondary metabolites (Al-Shaibani et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Actinomycetes play a crucial role in the production of various bioactive secondary metabolites. Research has shown that hypersaline soil, rhizosphere soil, marine sediments, and deserts are rich sources of diverse secondary metabolites due to the presence of Actinomycetes species, especially those found in near-extreme conditions, which are highly valued for their potential in novel secondary metabolite production (Khan et al, 2022). Efforts have been made to explore new habitats for screening actinomycete strains capable of producing novel secondary metabolites (Al-Shaibani et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Hizmet covers all the participants' financial costs ( van Bruinessen 2010). During these conferences, often organised together with academic or private partners, the movement's peace-building and charitable activities are particularly highlighted, and these themes are also regularly discussed in the books, articles, and pamphlets they publish (Yükleyen 2012;Khan and Khan 2018).…”
Section: Hizmetmentioning
confidence: 99%
“… See Carroll (2007);Hunt and Aslandoğan (2007);Yilmaz (2007);Çelik (2010);Ebaugh (2010);Esposito and Yilmaz (2010);Khan and Khan (2018);Alam (2019). 8 See e.g.,Gülen (1994;2010a;2010b).Thijl Sunier -978-90-04-68492-8 Downloaded from Brill.com 06/02/2024 02:54:32AM via Open Access.…”
mentioning
confidence: 99%
“…Through two key signaling pathways, NF-κB is activated in response to immunological and stress stimuli. 65 Additionally, NF-κB is essential for healthy immune responses to infections, but aberrant NF-κB activation is a significant contributor to inflammatory disorders. Blocking this pathway is a viable strategy for the prevention of unfavorable cardiac remodeling because activation of NF-κB is closely associated with the emergence of heart expansion and hypertrophy.…”
Section: Nuclear Factor-kappa B (Nf-κb)mentioning
confidence: 99%